2017
DOI: 10.1021/acs.analchem.6b04921
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of a Thin Oxide Film Formation from the Combination of Surface Reflectivity and Electrochemical Methods

Abstract: Electrochemical methods (cyclic voltammetry (CV), potential steps, and electrochemical impedance spectroscopy) were successfully combined with in situ reflectometry measurements for a detailed analysis of the passive layer evolution as a function of the electrode potential. Interestingly, both EIS and surface reflectivity allowed a film thickness in the nanometer range to be readily determined. In addition, transient analyses of the reflectivity simultaneously recorded with CVs show the formation of both FeO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…The capacitance of the oxide film can be extracted from the impedance data by using the complexcapacitance representation [58,59] and then, the oxide film thickness can be calculated. It was shown that this methodology allows an easy determination of the oxide film thickness that agrees well with the results obtained with other techniques, such as XPS [38] or reflectometry [41]. A similar methodology has been recently used to investigate the stability of the oxides film formed on a Mg alloy containing rare-earth elements [42].…”
Section: Interfacial Capacitance: Graphical Analysis and Power-law Modelsupporting
confidence: 70%
“…The capacitance of the oxide film can be extracted from the impedance data by using the complexcapacitance representation [58,59] and then, the oxide film thickness can be calculated. It was shown that this methodology allows an easy determination of the oxide film thickness that agrees well with the results obtained with other techniques, such as XPS [38] or reflectometry [41]. A similar methodology has been recently used to investigate the stability of the oxides film formed on a Mg alloy containing rare-earth elements [42].…”
Section: Interfacial Capacitance: Graphical Analysis and Power-law Modelsupporting
confidence: 70%
“…Comparing the signal recorded at each pixel I(x,y,t) to that recorded on the first image I(x,y,t = 0) allows monitoring of the local relative variation in reflectivity, ∆R(x,y,t)/R, from, Under the λ = 490 nm blue light illumination used herein, an ideal reflecting Au substrate ( ñ M . = 1.1 + 1.83i) immersed in water (n A = 1.33) is expected to reflect toward the CCD camera 37% of the incident light, and our setup was shown to detect local variation of reflectivity down to ∆R/R = 0.002 [16][17][18], meaning variation in collected signal down to 0.2%.…”
Section: Principle Of the Reflectivity Measurementmentioning
confidence: 80%
“…As a perspective of this work, reflectance microscopy is a simple yet powerful tool that has allowed monitoring electrochemical processes [15][16][17][18]63]. It does not require a transparent electrode unlike methods relying on darkfield illuminations, it is not restricted to Au electrodes, but to many reflecting surfaces [18], and can be performed at standard glass-insulated microelectrodes [16], or be coupled to local probing such as STM [63]. Based on these reported results, we expect that the technique could be applied to imaging the electrochemical reactivity of a wide range of NPs at the single entity level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations